2020
DOI: 10.24251/hicss.2020.604
|View full text |Cite
|
Sign up to set email alerts
|

Why People Adopt Vr English Language Learning Systems: An Extended Perspective Of Task-Technology Fit

Abstract: Virtual Reality (VR) techniques involving immersion, interaction, and imagination, not only can improve conventional teaching methods, but also can enhance the transmission of education training contents through the interaction and simulation characteristics of VR. Incorporating information technology (IT) with English teaching has become an important issue in the academic field. Emerging after computer-assisted teaching, interactive network learning, distance education, and mobile learning in the early days, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Digital learning technology is thought to help students improve learning and tend to be motivated when they enter work [24]. This was also proven by [25] who found that those who have experience using a technology continuously will have a positive effect on how easy it is to use and apply. According to [26] the success of the e-learning system depends on the cooperation between the ICT center, the responsible center, and the leader responsible for introducing ICT-based learning to understand the next [27].…”
Section: Literature Reviewmentioning
confidence: 92%
“…Digital learning technology is thought to help students improve learning and tend to be motivated when they enter work [24]. This was also proven by [25] who found that those who have experience using a technology continuously will have a positive effect on how easy it is to use and apply. According to [26] the success of the e-learning system depends on the cooperation between the ICT center, the responsible center, and the leader responsible for introducing ICT-based learning to understand the next [27].…”
Section: Literature Reviewmentioning
confidence: 92%
“…Goodhue and Thompson (1995) added that an IT system can only be adopted when its functionality meets the needs of the task. In other words, when the task and technology are fit, users' performance can be strengthened (Wang and Lin, 2020). The TTF consists of the relationship between individuals, tasks requirement, and technology characteristics Goodhue and Thompson, 1995).…”
Section: Task-technology Fitmentioning
confidence: 99%